A decade of labour market reforms in the EU: Insights from the LABREF database - Alessandro Turrini; Gabor Koltay; Fabiana Pierini; Clarisse Goffard; Aron Kiss (Institute for the Study of Labor (IZA), 2014)
This paper analyses the determinants and impact of labour market reforms in the European Union over the period of 2000-2011. The source of information on reforms is the LABREF database developed in DG ECFIN of the European Commission in cooperation with the Economic Policy Committee of the ECOFIN Council. The database collects information on measures adopted by EU Member States. Despite limitations of count data on reform events, the evidence permits a number of interesting insights. The 2008 crisis triggered increased policy activity in most policy domains in a large number of EU countries, in particular in domains with macro-structural relevance (employment protection legislation, unemployment benefits, wage setting). Reforms tend to be more frequently carried out in countries characterised by disappointing labour market outcomes and a high initial level of regulation or fiscal burden on labour. Econometric evidence on the effects of selected reforms on aggregate labour market outcomes is broadly supportive of common priors: tax and benefit reforms tend to be followed after a time lag, by improved activity rates and lower unemployment.
Keywords: J20; J38; J48; J58; J68; 330; labour market; labour market reform; unemployment; financial crisis; European Union